Binder-free graphene oxide doughs - Che-Ning Yeh (Nature Portfolio, 2019)
Graphene oxide (GO) dispersions may be used as starting materials for graphene-based architectures. Here, a malleable and versatile dough state of GO is discovered, completing the GO–water continuum, which can be diluted or converted to glassy GO or graphene solids without long-range stacking order with enhanced mechanical and electrochemical properties